Modelling of the Silicon-On-Insulator microdosimeter response within the International Space Station for astronauts' radiation protection. (September 2019) - Peracchi, S.; Vohradsky, J.; Guatelli, S.; Bolst, D.; Tran, L.T.; Prokopovich, D.A.; Rosenfeld, A.B.
Abstract: Astronauts are exposed to high-energy cosmic radiation which may have harmful health effects. At the altitude of the International Space Station (ISS), the main radiation sources are Galactic Cosmic Rays (GCRs), Solar Particle Events (SPEs) and trapped protons of the Van Allen Belts. The radiation field mainly consists of protons, helium nuclei and heavy ions with energies up to hundreds of GeV/n. A powerful approach to determine the effect of space radiation on astronauts is microdosimetry. The Centre for Medical Radiation Physics is active in the development of Silicon-On-Insulator (SOI) microdosimeters, as an alternative to Tissue Equivalent Proportional Counters (TEPCs) for radiation protection purposes. SOI microdosimeters are portable and do not require a high-voltage power supply. They consist of a matrix of silicon Sensitive Volumes (SV), which mimic the dimensions of biological cells. In this study, we investigated for the first time the response of the 3D "Mushroom" microdosimeter, a type of SOI microdosimeter in the Columbus module of the ISS. Tissue-equivalent microdosimetric spectra of GCRs, SPEs, and trapped protons were obtained to estimate the dose equivalent delivered to the astronauts. Results demonstrate a non-negligible production of secondary particles due to the propagation of space radiation through the wall of the Columbus and the microdosimeter. A number of heavy ions were detected with high lineal energies, these events pose a significant hazard in terms of radiation protection. Moreover, the dose evaluation shows a good agreement with experimental data found in the literature, confirming the suitability of our Geant4 model and the feasibility of using the SOI microdosimeter for ISS astronauts' personal dosimetry. Highlights: A Geant4 model has been implemented for simulating the radiation environment at the ISS altitude. Microdosimetric spectra of GCRs, SPEs, and trapped protons have been retrieved as output from the GEANT4 simulation. The production of secondaries due to the propagation of primary particles though the spacecraft's shielding wall is relevant. SOI are advantageous for dose monitoring in space thanks to small dimensions, portability, low voltage and accuracy in characterizing the field.